2013
DOI: 10.1155/2013/651323
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of Plasma Cell-Free DNA1in Predicting Therapeutic Efficacy of Sorafenib on Metastatic Clear Cell Renal Cell Carcinoma

Abstract: Abstract. PURPOSE:The objective of this study is to determine whether or not plasma cfDNA levels can predict efficacy of sorafenib in patient with metastatic cRCC. MATERIALS AND METHODS: Plasma cfDNA levels were quantified by quantitative real-time PCR at six different time-points (before treatment, 4 weeks, 8 weeks, 12 weeks, 16 weeks, and 24 weeks) in 18 metastatic cRCC patients receiving sorafenib, as assessed by CT examination according to RECIST 1.1. RESULTS: A significantly lower plasma cfDNA level, meas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 22 publications
(23 reference statements)
3
31
0
1
Order By: Relevance
“…In line with these results, cfDNA levels in human cancers decreased in patients with response to radiotherapy and showed stable or increasing values in progressive patients [54]. The results of this first study were later confirmed in patients with lung cancer undergoing chemotherapy [55][56][57], in patients with rectal cancer receiving neoadjuvant radiochemotherapy [58], in patients with ovarian cancer treated by chemotherapy [59,60] and in patients with renal cancer treated by tyrosine kinase inhibitors [61]. However, it has to be mentioned that some minor studies with lower numbers of patients reported no association between cfDNA kinetics and tumor relapse or treatment response [37,62].…”
Section: Cfdnasupporting
confidence: 62%
“…In line with these results, cfDNA levels in human cancers decreased in patients with response to radiotherapy and showed stable or increasing values in progressive patients [54]. The results of this first study were later confirmed in patients with lung cancer undergoing chemotherapy [55][56][57], in patients with rectal cancer receiving neoadjuvant radiochemotherapy [58], in patients with ovarian cancer treated by chemotherapy [59,60] and in patients with renal cancer treated by tyrosine kinase inhibitors [61]. However, it has to be mentioned that some minor studies with lower numbers of patients reported no association between cfDNA kinetics and tumor relapse or treatment response [37,62].…”
Section: Cfdnasupporting
confidence: 62%
“…Higher cfDNA levels during the course of treatment also indicated poor prognosis [13]. Another study found that plasma cfDNA levels were elevated in metastatic RCC relative to localized disease and could predict postoperative recurrence with 91% sensitivity and 100% specificity [14].…”
Section: Clinical Applications Of Cell-free Dnamentioning
confidence: 99%
“…Feng et al [62] showed that high levels of circulating cell-free DNA (cfDNA) were associated with a poor response to sorafenib in 18 Chinese mRCC patients. Aziz et al [63] reported that a high microvessel area was associated with a better response on sorafenib; smaller primary tumors were observed (P = 0.005) [63].…”
Section: Sorafenibmentioning
confidence: 99%